Cambridge theology in the nineteenth century: enquiry, controversy and truth - Thompson, David Michael (Ashgate, 2008)
The end of the eighteenth century -- Herbert Marsh and the beginning of biblical criticism -- Evangelicals, Protestants and Orthodox -- The Coleridgean inheritance -- Theological reconstruction : historical criticism -- Theological reconstruction : atonement, incarnation, and church -- Some non-conformist voices